PENERAPAN METODE SINGLE EXPONENTIAL SMOOTHING UNTUK PREDIKSI PENGGUNAAN JASA KONSULTAN PAJAK: Application of The Single Exponential Smoothing Method for Prediction of The Use of Tax Consultant Services - Sarbaini, Sarbaini; Zukrianto, Zukrianto (Yayasan Al-Amin Qalbu, 2024)
This research was conducted based on the low number of tax employees in helping taxpayers carry out their tax obligations. This results in some taxpayers using the services of tax consultants. Taxpayers expect tax consultants to be able to help and solve tax problems that are being pursued by taxpayers. The purpose of this study is to foresee the use of services in the coming month at the tax consultant's office Rahmat Accountax. The method used in this study is a quantitative method. The data is processed in the form of quantitative data in the form of months, years, and the number of people who use services at the Rahmat Accountax office in January 2020-March 2022. This research is to predict the development of service use with the Single Exponential Smoothing (SES) method. The Single Exponential Smoothing method is a method used in short-term forecasting that is usually only 1 month ahead which assumes that the data fluctuates around a fixed mean value without a trend or consistent growth pattern. From the analysis that has been carried out, the author can conclude that the forecasting of service use at Rahmat Accountax has decreased from the previous month, namely as many as 8 clients to 7 clients with α=0,2